El florón como parte de la cultura popular lúdica y como metáfora a la problemática social contemporánea - Murillo Cabanilla, Raiza Mishell (2015)
Rapid technological growing in our present has generated a number of benefits but also difficulties, many of the once popular recreational activities have been gradually consumed like a candle. A clear example of this is the ignorance on the part of girls on the finial. At that it has been proposed to produce a happening by recording of video art in order to justify the loss of the cultural value of the statement proposing game and allows content to serve as experiences in art. To this it has been taken as a reference to relate concepts as the problem of trafficking in women or trafficking in women for sexual exploitation. The methodology used in this project is both deductive and inductive was characterized as being a documentary bibliographical research by using interviews and bibliographic records for proper presentation. I resulting in diverse characteristics that increased the progress of this text and in turn was obtained conclusion the desire to keep alive these recreational experiences based on very different media to various sensory games ideas. As for the various educational units implement more about these types of games in order to ward off infants of several problems in the web it is recommended.